Effects of water on the mechanical properties of silica glass using molecular dynamics. (1st October 2019) - Mei, Hai; Yang, Yongjian; van Duin, Adri C.T.; Sinnott, Susan B.; Mauro, John C.; Liu, Lisheng; Fu, Zhengyi
Abstract: Understanding the effects of water on the mechanical properties of silica glass is important for many applications of silicate glasses. In this study, the effects of water on both elastic and plastic properties of pure silica glass are investigated. The introduction of molecular water leads to an increase of Young's modulus of silica glass at low water content, while hydroxyl exhibits an opposite effect. While hydroxyl groups decrease both strength and fracture toughness of the glass via destructing the silica network connectivity, molecular water undermines these properties by effectively driving the silica network to a "strained" configuration in absence of external stress. The water effect can be characterized in terms of the change of Si-O bond length and Si-O-Si bond angle. The plateau in the stress-strain curves of silica with the existence of molecular water in compact tension is associated with the Si-O bond breaking followed by formation of silanol groups. Moreover, the introduction of molecular water lowers the critical tensile stress where the plateau occurs. Graphical abstract: Image 1